Evaluating Job Training in Two Chinese Cities - Bidani, Benu (2012)
Recent years have seen a surge in work on the impacts of active labor market programs for numerous countries. However, little evidence has been presented on the effectiveness of such programs in China. Recent economic reforms, associated with massive lay-offs, and the accompanying public retraining programs make China fertile ground for rigorous impact evaluations. This study uses survey data from the two large industrial cities Shenyang and Wuhan, covering the period 1998 to 2000, to evaluate retraining programs for over 2,000 workers two years after they had been observed as displaced and unemployed. Using a comparison group design, this study is, to our knowledge, the first evaluation of its kind in China. The evidence suggests that retraining helped workers find jobs in Wuhan, but had little effect in Shenyang. The study raises questions about the overall effectiveness of retraining expenditures, and it offers some directions for policy-makers about future interventions to help laid-off workers.